Komunikasi Interpersonal Pengasuh di Panti Jompo dalam Konteks Psikososial Lansia - Nunik Listari Azharani; Ratri Rizki Kusumalestari (Bandung Conference Series: Journalism, 2025)
Abstract. The 8th psychosocial stage, the elderly enter ego integrity vs despair. Currently, many elderly in nursing homes do not have their psychosocial needs met. The purpose of this study is 1) Describe the communication style of caregivers in interacting with the elderly in the Kencana Sejahtera Nursing Home environment, 2) Describe the verbal and non-verbal messages of caregivers and the elderly at the Kencana Sejahtera Nursing Home Foundation, 3) Describe the barriers to interpersonal communication between caregivers and the elderly, 4) Describe the reasons for interpersonal communication to meet psychosocial development. This study uses Joseph A. Devito's interpersonal communication theory. The paradigm is constructivism, with qualitative methods, and a case study approach. The results obtained in this study are: The communication style provided by the caregiver is in the form of assertive communication, the use of verbal messages in the form of positive affirmations, instructions and motivation with non-verbal communication of eye contact, touch, gestures, and paralinguistics. Communication barriers are in the form of missing information, lack of patience of caregivers, and family problems. The use of this communication makes the elderly respond faster and become independent. Abstrak Tahap ke-8 pskososial, lansia memasuki integritas ego vs keputusasaan. Saat ini, banyak lansia di panti jompo tidak terpenuhi kebutuhan psikososialnya. Tujuan a penelitian ini adalah 1) Deskripsikan gaya komunikasi pengasuh dalam berinteraksi dengan para lansia di lingkungan Panti Jompo Kencana Sejahtera, 2) Mendeskripsikan pesan verbal dan non-verbal pengasuh dan lansia di Yayasan Panti Jompo Kencana Sejahtera, 3) Mendeskripsikan hambatan komunikasi interpersonal pengasuh dengan lansia, 4) Mendeskripsikan alasan komunikasi interpersonal memenuhi perkembangan psikososial. Penelitian ini menggunakan teori komunikasi interpersonal Joseph A. Devito. Paradigma yaitu konstruktivisme, dengan metode kualitatif, dan pendekatan studi kasus. Hasil yang didapatkan dalam penelitian ini yaitu: Gaya komunikasi yang diberikan pengasuh berupa komunikasi asertif, pengguaan pesan verbal berupa afirmasi positif, instruksi dan motivasi dengan komunikasi non verbal kontak mata, sentuhan, gerak tubuh, dan paralinguistik. Hambatan komunikasi berupa miss informasi, kurangnya kesabaran pengasuh, dan permasalahan keluarga. Penggunaan komunikasi ini membuat lansia menjadi lebih cepat memberikan respon dan mandiri.